Kommt der Messias doch nur einmal?: Eine Bemerkung zum Messiasbild der Syrischen Baruch-Apokalypse - Juhás, Peter (2025)
Cet article propose un examen attentif des différents passages de 2 Bar concernant le Messie. Une attention particulière est accordée à la question de savoir s’il y a deux phases messianiques, ou en d’autres termes deux venues du Messie dans le scénario eschatologique selon 2 Bar. Cette hypothèse est rejetée.
This article offers a closer look at the text passages of 2 Baruch concerning the Messiah. Special attention is paid to the question of whether there are two messianic phases, or in other words two comings of the Messiah in the eschatological scenario according to 2 Baruch. This question is negatively answered.